A Novel Pre-treatment Approach to Ulcerative Colitis in a Mouse Model - Vahid Pouresmaeil; Amir Hooshang Mohammadpour; Vahid Ariabod; Atena Pourtaji (Iranian Journal of Colorectal Research, 2022)
Background: Inflammatory Bowel Disease (IBD) is a complex multifactorial disease that includes two Crohn's disease and ulcerative colitis (UC). The UC characterized by inflammation, oxidative stress, and increased intestinal epithelial cell apoptosis. The present study aiming to investigate the protective potential of a combination of five safety products: Bromelain (BR), Silibinin (SB), Alpha-lipoic acid (ALA), Inulin (IN) and Sodium butyrate (BU) against UC. Methods: Seventy-two male Balb/c mice were divided into 9 groups, and administered for 14 days by a minimum effective dose of BR, SB, ALA, IN, BU or all together (PAC). Mesalazine (MZ) is used to compare the therapeutic effects of the compounds. Colitis was induced by rectal injection of acetic acid (4%) in 12th day. Blood and colon tissue were collected and the expression of inflammatory cytokines, and oxidative stress indices were examined using ELISA methods. The SPSS v.24 was used for data analysis.Results: All the therapeutic groups including BR, IN, BU, ALA, SB separately, partially improved histopathological changes due to colitis, but PAC treatment prior to colitis induction significantly (p<0.001), and more effectively alleviated the extent and intensity of the histological signs of cell damage including inflammation intensity, macroscopic and microscopic colon damage, and improved colitis. A significant decrease in inflammatory cytokines and oxidative stress indices also observed in the group treated with ALA, SB and PAC.Conclusion: This new drug combination (PAC) is more beneficial for the prevention of UC better than MZ that is a usual treatment of UC.